End-of-Life Care for Patients With Advanced Ovarian Cancer Is Aggressive Despite Hospice Intervention: A Population-Based Study. Issue 6 (July 2018) - Chiang, Jui-Kun; Hsu, Chun-Shuo; Lin, Chih-Wen; Kao, Yee-Hsin
Abstract : Objective: To date, few studies have examined end-of-life (EOL) care and healthcare costs for patients with ovarian cancer. We evaluated the effects of hospice care on the quality of EOL care and healthcare costs for patients with ovarian cancer in the final month of life. Materials and Methods: We conducted a population-based study and analyzed data from Taiwan's Longitudinal Health Insurance Database, which contains claims information for medical records of patients, healthcare costs, and insurance system exit dates: our proxy for death between 1997 and 2011. Results: A total of 176 women who died of ovarian cancer were investigated. Of these patients, 32 (18.2%) had received hospice care. Univariate analysis revealed that the patients with hospice care (H group) had lower proportions of intensive care unit admission (0% vs 15.3%) and cardiopulmonary resuscitation (0% vs 18.1%). The mean health care cost per person during the final month of life for H group was approximately 5.5% significantly higher than patients without hospice care (non-H group) (US 3121 ± 376 vs 2957 ± 347). The effects of hospice care on intensive care unit admission, receipt of cardiopulmonary resuscitation, and more than 1 emergency room visit could not be assessed because no cases of these 3 occurrences were observed among the H group by the multivariate regression model. No significant difference was observed between the H and non-H groups in terms of chemotherapy during the final 2 weeks of life. The H group had higher probabilities for more than 1 hospitalization and death in acute hospitals after adjusting for confounders. Conclusions: The aggressiveness of EOL cancer care and healthcare costs could not be offset in the final month of life among women with advanced ovarian cancer who received hospice care. The factors of more hospitalizations and dying in hospital warrant further investigation.